The White Prophet, Volume 2 (of 2) - Caine, Hall, Sir, 1853-1931; Woodville, Richard Caton, 1856-1927 (Salt Lake City, UT : Project Gutenberg, 2016)
"The White Prophet, Volume 2 (of 2)" by Sir Hall Caine is a historical novel written in the early 20th century. The book follows the intertwined lives of its central characters, Helena and Gordon, against a backdrop of political and personal conflict in the Sudan and Egypt. With themes of love, betrayal, vengeance, and the clash of cultures, it explores how individual actions can lead to sweeping consequences amid a volatile setting. At the start of the volume, Helena wakes to a tumultuous scene, as news arrives that Gordon, a key figure from her past, has arrived in Khartoum. Conflicted by her feelings for him and her current situation, she experiences an intense internal struggle, exacerbated by the implications of her recent actions that could lead to disaster for Ishmael, the man she is betrothed to. Meanwhile, Gordon grapples with his own emotions, haunted by the recognition of his role in Helena's misfortunes and the newfound reality of his imminent return to Cairo, which he believes could prevent an innocent man$1 (Bs downfall. The opening draws readers into a world of tension and impending tragedy as the characters navigate their flawed decisions amidst the fervor of political uprising and personal loyalties. (This is an automatically generated summary.)s
Release date is 2016-06-15
Produced by Al Haines
Keywords: British -- Egypt -- Fiction; Egypt -- Fiction